ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF EMTRICITABINE AND TENOFOVIR BY REVERSED-PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY IN BULK AND TABLET DOSAGE FORMS - Ahmad, Sufiyan; Mohammed Usman, Mohammed Rageeb (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: A simple rapid, accurate, precise, and reproducible validated reversed-phase high performance liquid chromatography method was developed for the determination of emtricitabine (EMB) and tenofovir (TEN) in bulk and tablet dosage forms. Methods: The quantification was carried out using symmetry Premsil C18 (250 mm×4.6 mm, 5 μm) Younglin (S.K.) gradient way using mobile phase comprising of methanol:water (70:30 v/v) pH 3 and a detection wavelength of 273 nm, and injection volume of 20 μL, with a flow rate of 1 ml/minutes. Results: In the developed method, the retention time of EMB and TEN were found to be 3.1667 minutes and 7.5000 minutes. The developed method was validated according to the International Conference on Harmonization (ICH) guidelines. Conclusion: The linearity, precision, range, robustness was within the limits as specified by the ICH guidelines. Hence, the method was found to be simple, accurate, precise, economic, and reproducible. Hence, it is worthwhile that the proposed methods can be successfully utilized for the routine quality control analysis EMB and TEN in bulk drug as well as in formulations.